3D Printing photo-induced lignin nanotubes/polyurethane shape memory composite. (February 2023) - Wang, Feng; Jiang, Man; Pan, Yu; Lu, Yuan; Xu, Wangjie; Zhou, Yufan
Abstract: The excellent flexibility, biocompatibility, and shape memory properties of polyurethane (PU) have attracted great attention to fabricate devices for application in the fields of electronics and biomedical, etc. However, it still consists a challenge to fabricate shape memory polymer (SMP) materials with complicated shapes in response to remote stimuli precisely and instantly. In this paper, we achieved ultraviolet light responsive SMP composites by direct ink writing (DIW) 3D printing shape memory polyurethane (SMPU) with introduction of the laboratory prepared lignin nanotube (LNT) as UV absorbent. We prepared lignin nanotube with uniform morphology by dissolving and then controllable molecular assembling way during dialysis in deionized water. The 3D printed SMP composite of PU/LNT was found to reach the shape recovery rate of 99% under UV radiation (370 nm) for 15 min. In addition, the tensile strength of the 3D printed SMP composite of PU/LNT is increased to 16.4 MPa, which is 131% higher than that of the pristine PU (7.11 MPa). It is worth noting that the glass transition temperature (Tg ) of the 3D printed SMP composite of PU/LNT changed steadily from 47 °C to 33 °C by increasing the LNT content to 9%, which endows the composites with much wider application feasibility. The exploration on photo responsive 3D printed SMP composites with accurate shape recovery rate provides new candidates to improve the development of biomaterials and intelligent robots. Highlights: We prepared lignin nanotube with uniform morphology by molecular assemly during dialysis in deionized water. Ultraviolet light responsive SMP composites were prepared by direct ink writing (DIW) 3D printing with lignin nanotubes (LNTs) as UV absorbent. The 3D printed UV responsive SMP composite exhibits high strength and tunable glass transition temperature.